(x + 3)^3 = (x + 3)(x + 3)(x + 3) = (x + 3)(x^2 + 6x + 9) = x^3 + 9x^2 + 27x + 27
x^2 - 7x + 15
_________________
(x+4)/ x^3 - 3x^2 - 13x + 78
- x^3 + 4x^2
----------------
- 7x^2 - 13x
- - 7x^2 - 28x
------------------
15x + 78
- 15x + 60
-------------
18
remainder = 18
Answer:
the first option
Step-by-step explanation:
I have attached the explanation. hope this help
You only need one if you follow a pattern of
top left dot
top middle dot
middle middle dot
middle left dot
bottom left dot
bottom middle dot
bottom right dot
middle right dot
top right dot